THE ROLE OF SOCIAL CAPITAL IN MARKETING PEANUTS IN PADAELO VILLAGE MALLAWA DISTRICT MAROS REGENCY - Nur Aisyah Ramadani S.; Amruddin; Nadir (AgriMu, 2026)
This study aims to determine the role of social capital in peanut marketing in Padaelo Village, Mallawa District, Maros Regency. This study used snowball sampling and purposive sampling techniques to determine informants. Snowball sampling was used to expand the number of informants until the data obtained was deemed sufficiently saturated, while purposive sampling was used to select informants deemed knowledgeable and understanding of the research problem. Data collection techniques used included in-depth interviews, observation, questionnaires, and documentation. The results showed that there are two peanut marketing channels: the first channel, where farmers sell peanuts to collectors, then to wholesalers, and then to consumers. The second channel, where farmers sell directly to wholesalers. Furthermore, social capital plays a crucial role in supporting peanut marketing. Elements of social capital, such as trust, networks, norms, and reciprocal relationships, can streamline the marketing process, strengthen cooperation between farmers and marketers, and improve access to market information. The trust established between farmers and traders fosters sustainable cooperative relationships, while social networks facilitate crop distribution. Furthermore, norms and reciprocal relationships contribute to increased solidarity and efficiency in marketing.